Freedom of Association, the right to organize and collective bargaining in the Namibian Correctional Service: recommendations for law reform - Shilinge, Foibe (Department of Commercial Law, 2024)
The study explores the laws, policies and practices that prohibit the Namibian Correctional Service from organising and bargaining collectively on terms and conditions of their employment contracts. The study made recommendations based on the findings. The study was motivated by the fact that Namibia as a member state of the International Labour Organisation has ratified conventions concerning the Right to Organise and Collective Bargaining (Convention No. 98 of 1949), and the Right of Freedom of Association (Convention No. 87 of 1949). Namibia ratified the two above-mentioned conventions on the 3rd of January 1995. Convention 87 and Convention 98 provide prison staff the right of freedom of association and the right to organise, and the right to bargain collectively. These rights are also enshrined in the Namibian Constitution that “all persons shall have the right to freedom of association”. However, the Namibian Correctional Service does not exercise these rights due to legislative exclusion. The Labour Act No. 11 of 2007 which provides for employers and employees to organise and bargain collectively does not apply to the Namibian Correctional Service. Despite many inquiries and advice from the Committee of Experts on the Application of Conventions and Recommendations that Namibia must take steps to ensure that the Correctional Staff enjoy the guarantees under the two above mentioned Conventions, the Correctional Service is still not enjoying the right of freedom of association and the right to organise and to bargain collectively. The research study employed a qualitative approach. The qualitative design enabled the researcher to gather secondary data from legislation, case laws, magazines, reports, and other relevant documents. Data were analysed using the desktop data analysis technique. The study revealed that stringent national laws; lack of National Supervisory Body oversight of the implementation of ratified Conventions; budget constraints; shortage of Human Resources; lack of commitment by stakeholders such as trade unions, Office of the Prime Minister; and the Ministry of Home Affairs, Immigration, Safety and Security; and the failure of the Ministry of Labour, Industrial Relations and Employment Creation to review and amend the Labour Act No. 11 of 2007 that prohibits the Namibian Correctional Service to enjoy the guarantees under Convention 98 and Convention 87, are all factors that obstruct the members of the Namibian Correctional Service to form and join a union. As a result, the Namibian Correctional Service members are vulnerable and prone to abuse in terms of unfair discrimination relating to promotion and remuneration; unfair dismissals, poor disciplinary and grievance procedures; poor employment conditions; poor working environment/conditions, and exploitation by the employer due to lack of collective agreements. The study recommends that the Namibian Legislature amend the Labour Act No.11 of 2007 and that the Commissioner-General revoke the Commissioner of Prisons' Directive 03/2008 to ensure the application of the two Conventions to the Namibian Correctional Service by promoting collective bargaining and effective protection against anti-union discrimination in the Namibian Correctional Service. Secondly, the Correctional Officers may pursue the matter in the competent Court of law to seek a declaratory order on the constitutionality of the provisions of the Labour Act No. 11 of 2007 and the Commissioner of Prison's Directive.